Biochemistry of Hormones. (Module 2, IV Semester) - Aleksandrova, K. V.; Levich, S. V.; Ivanchenko, D. G.; Александрова, Катерина Вячеславівна; Левіч, Сергій Вадимович; Іванченко, Дмитро Григорович (Zaporizhzhia state medical university, 2015)
Textbook was made in accordance with the program of biological chemistry for training of students of higher educational institutions of III-IV levels of accreditation for specialty 7.12010001 «General Medicine». This textbook is recommended to use for students of international department (the second year of study) for independent work at home and in class.